An extraction-free method by which a single slot blot can be used to quantify intracellular DNA damage (crosslinks or strand breaks) and changes in DNA damage response proteins or replication - Mary M. McHugh; Terry A. Beerman (BioTechniques, 2009)
We report an extraction-free assay in which the same slot blot membrane can be used to assess total genomic DNA damage (i.e., crosslinks or strand breaks) and DNA replication (i.e., bromodeoxyuridine incorporation) or protein levels (i.e., γ-H2AX). 14C-thymidine radiolabeling of HCT116 cells loaded directly on a Hybond N+ membrane slot blot enables the quantitation of DNA interstrand crosslinks and DNA breaks, while bromodeoxyuridine incorporation or levels of γ-H2AX can be assessed by incubating blots with primary monoclonal antibodies followed by detection with horseradish peroxidase (HRP) secondary antibodies. Uniform Ponceau staining of all samples on the membrane indicates that protein binding to the membrane is independent of DNA damage or elution. The use of a single membrane to assay levels of DNA damage and concomitant changes in damage response proteins or replication allows the direct quantitation of diverse parameters under identical conditions.